ENDOPHTHALMITIS IN ACEH: ANALYSIS OF MICROBIAL SPECTRUM AND ANTIBIOTIC RESISTANCE - Cut Putri Samira; Enny Nilawati; Lia Meuthia Zaini; Dian Islami; Putri Nabillah Mulya (Indonesian Vitreoretinal Society, 2026)
Introduction: Endophthalmitis is a rare but vision-threatening intraocular infection that requires prompt and appropriate antimicrobial therapy. The microbial spectrum and antibiotic resistance patterns vary by region, yet data from Aceh, Indonesia, are limited. This study aimed to analyze the microbial profile and antibiotic susceptibility patterns of endophthalmitis cases treated at a tertiary healthcare center in Aceh. Methods: A retrospective descriptive study was conducted using medical records of patients diagnosed with endophthalmitis at dr. Zainoel Abidin General Hospital, Banda Aceh, from January 2021 to December 2024. Data collected included demographics, predisposing factors, etiological classification, microbiological culture results, and antibiotic susceptibility profiles. Microbiological identification and susceptibility testing were performed using standard culture methods and the VITEK2 Compact system. Result: A total of 111 eyes with unilateral endophthalmitis were included. Exogenous endophthalmitis predominated (95.5%), with postâ€“cataract surgery (36.0%), traumatic (29.7%), and keratitis-related (27.1%) cases being most common. The mean patient age was 52.7 Â± 18.5 years, with male predominance (63%). Bacterial isolates were identified in 26 eyes (23.5%), with Gram-negative organisms accounting for 65.4%. Pseudomonas aeruginosa was the most frequently isolated pathogen (58.8%). Gentamicin showed the highest overall susceptibility (75.0%), while vancomycin demonstrated complete sensitivity against Gram-positive isolates. Conclusion: Endophthalmitis in Aceh is predominantly exogenous and commonly caused by Gram-negative bacteria, particularly Pseudomonas aeruginosa. Gentamicin demonstrated the highest in vitro activity, while vancomycin and ceftazidime remain key components of empirical intravitreal therapy to ensure broad antimicrobial coverage. These findings provide important local microbiological data to support evidence-based management of endophthalmitis.